"Not Some Other -ism"—On Some Western Marxist Misrepresentations of Chinese Socialism. Issue 2 (3rd April 2021) - Boer, Roland; Yan, Ping
ABSTRACT: This study tackles four Western Marxist misrepresentations of socialism with Chinese characteristics, particularly as it has developed with the reform and opening-up. Each of these misrepresentations sets in opposition the economy and the state, with the former being seen as "capitalist" (in some form) and the latter as variously "authoritarian, " "bureaucratic" or simply as "interventionist." In other words, "Chinese characteristics" designates the superstructural feature that determines—incorrectly in light of Marxist analysis—the economic base, which is mistakenly seen as capitalist. While each misrepresentation has its own distinct problems, they also have common problems: a voluntarist position on political decisions, which fails to provide any reason for a "capitalist turn"; the assumption that a "market economy, " wherever and whenever it appears, is by definition capitalist; the deployment of neocolonial and "Orientalist" assumptions coupled with a Western "betrayal narrative"; and a systemic neglect of Chinese language research. The conclusion provides a summarising assessment that focuses on the empirical flaws and methodological presuppositions of these misrepresentations. We emphasise that our focus is primarily on the internal problems and inconsistencies of these misrepresentations, although we also offer—where needed—some constructive alternatives.